Community-based physical activity-related health promotion in Germany Systematic review and good practice projects - Dippon, Lea; Helsper, Natalie; Kohler, Simone; Weber, Philipp; Rütten, Alfred; Pfeifer, Klaus; Birkholz, Leonie; Semrau, Jana (German Journal of Exercise and Sport Research, 2023)
Approaches to community-based physical activity-related health promotion (CPAHP) are recommended to counteract physical inactivity in the population. The aim of this article was to present a systematic review of CPAHP measures in Germany. Furthermore, we aimed to identify good practice projects to provide guidance for the implementation and scale up of CPAHP. In the first step, we identified projects by searching 4 scientific databases and 21 project databases. We then extracted data for "federal state ", "consideration of health equity " and "implementation in urban or rural areas ". In addition, we sorted the included projects into different approaches in the community setting. In the next step, we assessed projects with a documented process and/or outcome evaluation using quality criteria for the phases of conceptualization, implementation, and evaluation. Projects that fulfilled at least 50% of the quality criteria were selected as good practice projects. We identified a total of 240 CPAHP projects. Rural areas primarily implemented environmental approaches, while urban areas focused more on multicomponent approaches as well as offers and events. Overall, 45 projects showed adequate documentation of the process and/or outcome evaluation, of which 17 projects were identified as good practice. However, there is potential for improvement in addressing health equity, active participation of socially disadvantaged people over the entire project cycle, and implementation of multicomponent approaches. This requires funding programs that promote good-practice projects which establish structures and particularly reach disadvantaged communities. A jointly adopted standard by stakeholders from policy, practice, and research for the application of quality criteria along with a classification for good practice would be beneficial for further strategic development of CPAHP in Germany.
CRIS-Team WoS Importer:2023-03-17